(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article delves into the pedagogical views of Muhammadrizo Ogahi, an influential educator from Central Asia. Ogahi’s educational philosophy, teaching methods, and contributions to the field of education are examined. The study analyzes his impact on education in the region, shedding light on his innovative ideas and their relevance today.